2005
DOI: 10.1080/07853890510007278
|View full text |Cite
|
Sign up to set email alerts
|

C5b‐9 complement complex in autoimmune demyelination and multiple sclerosis: Dual role in neuroinflammation and neuroprotection

Abstract: Complement system activation plays an important role in innate and acquired immunity. Activation of complement leads to the formation of C5b-9 terminal complex. While C5b-9 can promote cell lysis, sublytic assembly of C5b-9 on plasma membranes induces cell cycle activation and survival. Multiple sclerosis (MS) and its animal model experimental allergic encephalomyelitis (EAE) are inflammatory demyelinating diseases of the central nervous system (CNS) mediated by activated lymphocytes, macrophages/microglia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…At a lower dose, C5b-9 can induce sublytic injury (i.e. cell apoptosis) (14), but some studies from mouse experimental allergic encephalomyelitis show that sublytic C5b-9 can protect oligodendrocytes from apoptosis and lead to survival (25,26), suggesting that the different roles in these cells may be due to different biochemical reactions, including cell states, upon sublytic C5b-9 attack (3,9,27).…”
Section: Discussionmentioning
confidence: 99%
“…At a lower dose, C5b-9 can induce sublytic injury (i.e. cell apoptosis) (14), but some studies from mouse experimental allergic encephalomyelitis show that sublytic C5b-9 can protect oligodendrocytes from apoptosis and lead to survival (25,26), suggesting that the different roles in these cells may be due to different biochemical reactions, including cell states, upon sublytic C5b-9 attack (3,9,27).…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models of EAE, injury and myelin loss is attenuated in animals deficient in C5 and C6 and increased in animals deficient in CD59a, an inhibitor of MAC formation. [27][28][29][30][31] A contradictory finding was reported, however, in a rat model of immunological demyelination in which intraspinal infusions of IgG antibodies were administered in the presence of serum deficient in either C3, C4, C5, C6, or factor B.…”
Section: Discussionmentioning
confidence: 99%
“…At autopsy, TBI patients have reported Aβ peptides and neurofibrillary tangles of hyperphosphorylated tau proteins, thus leading to the hypothesis that AD can possibly be a secondary effect of TBI [25]. A past study showed that an increase of neuronal C5a receptors and C5b-9 terminal complex, a promoter of the cell cycle and cell lysis, in diffuse axonal injury (DAI) of TBI, could lead to possible secondary neuronal cell death [26,27]. New studies show that the C5a receptors and C5b-9 terminal complex should be used as targeted treatment areas, but are not necessarily a source of secondary axotomy in DAI [28].…”
Section: Current Modelsmentioning
confidence: 99%